Maritime transportation as an instrument of ACS trade - Caribbean Community Secretariat (CCS GeorgetownGY, 1995)
Seeks to establish the current level of trade; the existing levels and direction (ports of call) of shipping services; and the constraints, in particular, the policy-related constraints to the provision of timely maritime transportation services. Makes recommendations on immediate and longer term actions to ameliorate the shipping problems.